2017
DOI: 10.1051/0004-6361/201629805
|View full text |Cite
|
Sign up to set email alerts
|

The GIRAFFE Inner Bulge Survey (GIBS)

Abstract: Context. Several recent studies have demonstrated that the Galactic bulge hosts two components with different mean metallicities, and possibly different spatial distribution and kinematics. As a consequence, both the metallicity distribution and the radial velocity of bulge stars vary across different lines of sight. Aims. We present here the metallicity distribution function of red clump stars in 26 fields spread across a wide area of the bulge, with special emphasis on fields close to Galactic plane, at lati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
260
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(301 citation statements)
references
References 57 publications
41
260
0
Order By: Relevance
“…We see that M1 is compatible with the APOGEE data, which points to low metallicities of on average ∼ -0.1 dex (and see also Zoccali et al 2017).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…We see that M1 is compatible with the APOGEE data, which points to low metallicities of on average ∼ -0.1 dex (and see also Zoccali et al 2017).…”
Section: Resultssupporting
confidence: 81%
“…Calura et al 2012;Obreja et al 2013) and the origin of its various stellar populations, as revealed by its broad metallicity distribution function (MDF;McWilliam & Rich 1994;Hill et al 2011;Ness et al 2013;Rojas-Arriagada et al 2014;Zoccali et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zoccali et al (2017) parametrized the metallicity distribution in each of the 26 fields of the GIBS survey into a metal-poor and a metal-rich component. They presented a density map for each of the two components for −10 • < l < 10 • and −10 • < b < 10 • showing that the metal-poor population is more centrally concentrated than the metal-rich one, and has a more axisymmetric spatial distribution.…”
Section: Trends In the Chemical Distributionmentioning
confidence: 99%
“…Bulges of galaxies, once thought to be simple systems supported by velocity dispersion, have been reported to be more complex structures, with bars, pseudo-bulges, classical bulges, etc.,2013; Johnson et al 2012;Ness et al 2012;Zoccali et al 2008Zoccali et al , 2016. Recent observations have reported the existence of very old stars traced by RR Lyrae populations , as well as young stars (Dékány et al 2015), within the bulge region.…”
Section: Introductionmentioning
confidence: 99%
“…The Milky Way (MW) offers a unique perspective to test models of galaxy formation because stars can be individually observed and their properties, such as kinematics, dynamics, and chemical composition, can be more accurately derived in the four main stellar components: bulge, thin and thick discs and stellar haloes (see Bland-Hawthorn & Gerhard 2016, for a detailed discussion of the MW components). The copatricia.tissera@unab.cl existence of these components in the central region is now being explored in more detail as the result of larger and more precise observational data in the bulge (e.g., Gran et al 2016;Zoccali et al 2016), stellar halo (e.g., Santucci et al 2015;Carollo et al 2016;Helmi et al 2016) and the disc (e.g., Minniti et al 2017). …”
Section: Introductionmentioning
confidence: 99%